The Penetration of CCA Preservative on four under-utilized Malaysian hardwood species - Sahri, Mohd Hamami; Ling, Kwong Hung; Harun, Jamaluddin; Ahmad, Faujan (Universiti Putra Malaysia Press, 1993)
Four under-utilized Malaysian hardwood species, namely Mempening (Lithocarpus spp.), Nyatoh Nangka Kuning (pouteria malaccensis (Clarke) Baehni), Pauh Kijang (lrvingia malayana Oliv.) and Petai (Parkia speciosa Hassk.) were selected for the treatability study. Two popular timber species, namely Jelutong (Dyera costulata Hk. f.) and Merbau (lntsia palembanica Miq.) were included as controls. The moisture content and density of all the selected timbers were determined prior to the treatment. All the seasoned specimens were vacuum pressure treated with three per cent copper-chrome-arsenate (CGA) preservative (Celcure "A'j solution. There is a general correlation between the density (specific gravity) of wood and the penetration of CGA-preservative. Petai exhibited the deepest side penetration (5.0) followed lJyJelutong (4.9), Nyatoh Nangka Kuning (3.6), Mempening (1.75), Pauh K~'ang (1.5) and Merbau (0). Lower density timber species (Jelutong, Nyatoh Nangka Kuning and Petai) attained deeper penetration when compared to higher density timber species (Mempening, Merbau and Pauh Kijang). Significant differences in side penetration were found among the six species. The four under-utilized Malaysian hardwood species are amenable to the vacuum-pressure treatment with CGA preservative.